2010
DOI: 10.1590/1808-1657v77p7112010
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência De Salmonella Spp. E Staphylococcus Coagulase Positiva Em Pescado No Nordeste, Brasil

Abstract: RESUMO O presente estudo foi conduzido com o objetivo de verificar a ocorrência de Salmonella spp. e Staphylococcus coagulase positiva em pescados e crustáceos provenientes da região nordeste no período de fevereiro de 2004 a dezembro de 2005. Das 143 amostras de peixes e crustáceos (camarão congelado e cauda de lagosta), 5 (3,5%) apresentaram-se positivas para Salmonella spp. Enquanto nas amostras de peixe e cauda de lagosta a contagem de Staphylococcus coagulase positiva foi < 1,0 x 102UFC/g estimado, nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
0
1
Order By: Relevance
“…On the other hand, the results of those studies are higher than those reported in Venezuela, where a 2% frequency for raw shrimp was reported (29). In addition, other studies have also reported prevalence rates of 1.8% a 5.71% in shrimp (29,(30)(31)(32), which are much lower than our results (64.1%).…”
Section: Discussioncontrasting
confidence: 97%
“…On the other hand, the results of those studies are higher than those reported in Venezuela, where a 2% frequency for raw shrimp was reported (29). In addition, other studies have also reported prevalence rates of 1.8% a 5.71% in shrimp (29,(30)(31)(32), which are much lower than our results (64.1%).…”
Section: Discussioncontrasting
confidence: 97%